Danny the champion of the world - Dahl, Roald; Blake, Quentin (Puffin London, 2016)
CLASSIC FICTION (CHILDREN'S / TEENAGE). Phizz-whizzing new branding for the world's No.1 storyteller, Roald Dahl! Exciting, bold and instantly recognisable with Quentin Blake's inimitable artwork. Danny lives in a gipsy caravan with his father, the most marvellous and exciting father any boy ever had. All the land around them belongs to Mr Victor Hazell, a rich snob with a great glistening beery face and tiny piggy eyes. Nobody likes him, not one-little bit. So one day, Danny and his father concoct a daring plot that will give the old blue-faced baboon Victor Hazell the greatest shock of his life - so long as they don't get caught... Ages 9+